All Days 1992
DOI: 10.2118/24114-ms
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Minimum Miscibility Pressure: Slim-Tube or Rising-Bubble Method?

Abstract: Measurements of carbon dioxide minimum miscibility pressures (MMP) using a slim tube apparatus were compared with those using a rising-bubble apparatus (RBA). MMPs were measured for twelve different oils, with gravities varying from 34° API to 51° API. The results were found to compare very well when using a specific criterion for the slim-tube MMP. Although the slim tube method is often referred to as the industry standard, there is no standard design, no standard operating procedure, and no standard criterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 31 publications
4
74
0
2
Order By: Relevance
“…[2,6] The slim-tube displacement method is the most commonly used technique among the proposed experimental methods used for determining the MMP. [7,8] However, this method is relatively expensive and time consuming. There are also some other experimental methods such as rising bubble apparatus (RBA) and vanishing interfacial tension (VIT) by means of which the MMP can be more easily measured.…”
Section: Introductionmentioning
confidence: 99%
“…[2,6] The slim-tube displacement method is the most commonly used technique among the proposed experimental methods used for determining the MMP. [7,8] However, this method is relatively expensive and time consuming. There are also some other experimental methods such as rising bubble apparatus (RBA) and vanishing interfacial tension (VIT) by means of which the MMP can be more easily measured.…”
Section: Introductionmentioning
confidence: 99%
“…Our interpretation was based on the definition of MMP as the break in slope from the plot of cumulative oil recovery (in percentage) at 1.2 pore volume of injected gas against displacement pressure (Elsharkawy et al, 1992). The instantaneous pore volume of injected gas at any stage i (where i = 1, 2, 3…) was calculated using the following equation;…”
Section: Resultsmentioning
confidence: 99%
“…They considered color degradation from dark oil to yellow fluid as an indication of multi-contact miscibility whereas the production of clear vapor and dark oil implied immiscible flood (Yellig et al, 1980). Elsharkawy et al (1992) assumed MMP to be the break-over pressure in the plots of oil recovery at gas breakthrough or at 1PV to 1.2PV of injected gas or ultimate oil recovery against displacement pressure. However, if the break-over is not sharp, the authors suggested taking MMP as the pressure for which incremental oil recovery per incremental pressure increase is less than some arbitrary value (Elsharkawy et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations